2021
DOI: 10.1126/sciadv.abg7607
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 can recruit a heme metabolite to evade antibody immunity

Abstract: The coronaviral spike is the dominant viral antigen and the target of neutralizing antibodies. We show that SARS-CoV-2 spike binds biliverdin and bilirubin, the tetrapyrrole products of heme metabolism, with nanomolar affinity. Using cryo–electron microscopy and x-ray crystallography, we mapped the tetrapyrrole interaction pocket to a deep cleft on the spike N-terminal domain (NTD). At physiological concentrations, biliverdin significantly dampened the reactivity of SARS-CoV-2 spike with immune sera and inhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
183
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(199 citation statements)
references
References 87 publications
15
183
1
Order By: Relevance
“…The copyright holder for this preprint (which this version posted April 26, 2021. ; https://doi.org/10.1101/2021.04.23.441209 doi: bioRxiv preprint cells 38 , could be associated with the escape from the T-cell immunity. Furthermore, recent evidence suggests that this region contains an additional epitope for antibody binding 39 . Because these insertions were detected only in recent samples, it appears that the respective variants have to be further monitored.…”
Section: Insertions In the S Protein Produce Putative Antibody Escape Variantsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 26, 2021. ; https://doi.org/10.1101/2021.04.23.441209 doi: bioRxiv preprint cells 38 , could be associated with the escape from the T-cell immunity. Furthermore, recent evidence suggests that this region contains an additional epitope for antibody binding 39 . Because these insertions were detected only in recent samples, it appears that the respective variants have to be further monitored.…”
Section: Insertions In the S Protein Produce Putative Antibody Escape Variantsmentioning
confidence: 99%
“…The authors concluded that such a pocket can be considered a “potential target for drug design against SARS-CoV-2”. Remarkably, while the present paper was under review, Rosa et al [ 57 ] showed, using cryo-electron microscopy and X-ray crystallography, that two small molecules (i.e., the products of heme metabolism biliverdin and bilirubin) target the SARS-CoV-2 S protein with nanomolar affinity by interacting with P2. In summary, the computed size, degree of enclosure, hydrophobicity, and druggability, combined with some recent experimental observations, put forward P2 as a relevant site for further structure-based drug discovery approaches to be followed to identify new small molecules able to bind the SARS-CoV-2 S protein.…”
Section: Resultsmentioning
confidence: 90%
“…We found that mAb PVI.V6-14 belongs to an as of yet undescribed class of antibodies that bind within a hydrophobic cavity, previously identified to bind a heme metabolite, biliverdin 32 . Our functional binding and neutralization data confirm that the antibody competes with biliverdin and also underscores the antibody's capacity to recognize emerging viral variants of concern.…”
Section: Introductionmentioning
confidence: 94%
“…A previous study reported the structure of a heme metabolite, biliverdin, bound within the hydrophobic NTD pocket 32 . We superposed the structure of our Fab bound NTD with that of the biliverdin bound one and found that our antibody, through its HCDR3 aromatic amino-acid residues, was a molecular mimic of the tetrapyrrole molecule (Figure 3a).…”
Section: Antibody Pviv6-14 Directly Competes With and Is Inhibited By Biliverdinmentioning
confidence: 99%